The destructive 1790 Oran (NW Algeria) earthquake in a region of low seismicity - Buforn, Elisa (2019)
The Oran earthquake of 9th October 1790 in NW Algeria caused heavy damage in that city, and originated a tsunami observed in Almeria and Cartagena, SE Spain. It occurred in a region of low seismicity in comparison with other regions east of Algeria. The abundant contemporary documentation analysed in the present study, some of it not used previously, confirms a maximum intensity of IX–X (EMS-98) for Oran city. The estimated focal parameters are: origin time 01 h 15 m or 01 h 30 m UT, duration 1-to-2 min, a macroseismic offshore epicentre at 35.9°N, 0.6°W to explain the generation of the tsunami, and estimated magnitude 6.0–6.5. The rupture is complex, formed by two events, and may have been associated with NE-SW oriented thrust faults present in the area.